2011
DOI: 10.3384/ecp11057232
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Research on Jatropha Curcas Plantation Management

Abstract: This paper will present the interactive research of expert team on Jatropha curcas plantation management to obtain high productivity in terms of dry seed weight per cultivation area. Set of experiments were designed and performed on randomize central block design and triplicate data were collected. The spacing was the important factor along with the cutting management program for long time cultivation. Therefore, the 3 different spacing (2x2, 2x3 and 3x3) were tested. The results show that 2x3 and 3x3 m spacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The planting of this species was motivated by the belief that it grows easily with minimal management requirements, but soil restoration and water conservation techniques improve the growth and survival rates on degraded soils (Kagamèbga et al, 2011;Iiyama et al, 2012). In plantation, spacing was the important factor along with the cutting management program for long time cultivation (Srinophakun et al, 2011). Thus, the productivity of J. curcas varies with genotypes, varieties and ecological conditions (Sosa-Segura et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The planting of this species was motivated by the belief that it grows easily with minimal management requirements, but soil restoration and water conservation techniques improve the growth and survival rates on degraded soils (Kagamèbga et al, 2011;Iiyama et al, 2012). In plantation, spacing was the important factor along with the cutting management program for long time cultivation (Srinophakun et al, 2011). Thus, the productivity of J. curcas varies with genotypes, varieties and ecological conditions (Sosa-Segura et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is popularly reported that pests and diseases do not pose a significant threat to jatropha, due to the insecticidal and toxic characteristics of all parts of the plant. However, incidence of pests and diseases such as collar rot, leaf spots, root rot and damping-off, may be controlled with a combination of cultural techniques (for example, avoiding waterlogged conditions) and fungicides are widely reported [2]. In Nicaragua (Pachycoris klugii) and India (Scutellera nobilis), causes flower fall, fruit abortion and seed malformation.…”
Section: Pests and Diseasesmentioning
confidence: 99%
“…One liter of J. curcas L. oil comes from about 4 kg of seed which will give about 3 kg of the seed cake, a pressed seed cake, left after oil extraction [2].…”
Section: Seed Cakementioning
confidence: 99%
See 2 more Smart Citations